Memahami Desa Wisata Berkelanjutan Berbasis Partisipasi Masyarakat - Muhammad Lukman; Nita Aribah Hanif; Sierfi Rahayu; Tiwi Riskiyani; Yeni Khoirunnisa Agustiani; Dwisapto Yusuf Pradana; Fat’chatus Chanifa Jikhan (Journal of Social Contemplativa, 2026)
The development of sustainable tourism villages based on community participation is a crucial strategy in transforming Indonesian tourism towards a more inclusive and resilient model. This study aims to analyze the dimensions of sustainability and the dynamics of community participation in the tourism village ecosystem through a literature review and qualitative methods. The findings indicate that community participation often remains at the level of tokenism (informing and consultation) according to Tangga Arnstein, where substantive involvement in decision-making is still limited. Synergy between Tourism Awareness Groups (Pokdarwis) and Village-Owned Enterprises (BUMDes) plays a crucial role in conflict management and the equitable distribution of economic benefits. Although national policy instruments have referred to global standards (GSTC), challenges such as low human resource capacity, limited capital, and the risk of cultural commodification remain major obstacles. The study concludes that the transformation towards independent tourism villages requires strengthening digital literacy (Tourism 5.0) and integrating local wisdom values ​​such as Tri Hita Karana to ensure a balance between economic, socio-cultural, and environmental aspects.